2008
DOI: 10.1002/bies.20838
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding bad genes: oxidatively damaged DNA in germ line and mate choice

Abstract: August Weismann proposed that genetic changes in somatic cells cannot pass to germ cells and hence to next generations. Nevertheless, evidence is accumulating that some environmental effects can promote heritable changes in the DNA of germ cells, which implies that some somatic influence on germ line is possible. This influence is mostly detrimental and related to the presence of oxidative stress, which induces mutations and epigenetic changes. This effect should be stronger in males due to the particular char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 107 publications
4
114
0
Order By: Relevance
“…Our results provide a first supporting step for the predictions of Beck & Promislow (2007) and Velando et al (2008) using crickets as a model organism. Females showed strong preference for the secondary sexual traits of young males, which decline in attractiveness as they age, probably because of senescence of somatic cells (flight muscles).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Our results provide a first supporting step for the predictions of Beck & Promislow (2007) and Velando et al (2008) using crickets as a model organism. Females showed strong preference for the secondary sexual traits of young males, which decline in attractiveness as they age, probably because of senescence of somatic cells (flight muscles).…”
Section: Resultssupporting
confidence: 58%
“…If the secondary sexual traits preferred by females are honest indicators of male quality, increasing somatic oxidative damage with age will increasingly have a negative effect on the expression of these traits. In line with the predictions of Beck & Promislow (2007) and Velando et al (2008), Hoikkala et al (2008) showed that both reproductive success and the quality of sexually selected song in Drosophila montana males decrease with male age. Female D. montana are therefore able to avoid 'bad genes' by preferring younger males on the basis of the courtship song.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Oxidative stress can have potentially severe negative impacts on male sperm quality [7,76,77], which may decrease the fecundity benefits of signalling because males are less likely to convert any attraction of females into successful fertilizations. For example, both the percentage of motile sperm and sperm swimming ability can correlate negatively with oxidative stress [78,79], suggesting that oxidative stress may influence the functional characteristics of sperm.…”
Section: Oxidative Stress In the Twenty-first Centurymentioning
confidence: 99%